B-cell activating factor targeted therapy and lupus - Boneparth, Alexis (BioMed Central, 2012)
B-cell activating factor (BAFF), a member of the family of TNF-like cytokines, supports the survival and differentiation of B cells. The successful development of belimumab, a human antibody targeting soluble BAFF, has marked an important milestone in the development of biologic therapy for treatment of systemic lupus erythematosus (SLE), although much remains unknown regarding the clinical utility of BAFF inhibition in SLE and other autoimmune diseases. In the present review, we provide an overview of the knowledge concerning BAFF's role in murine and human B-cell development and maturation, as well as the clinical and mechanistic effects of BAFF inhibition in human SLE.